The Influence of Participatory Budgeting to Budgetary Slack in Local Government at Majene Regency - Husnha Almagfirah; Edy Fitriawan Syahadat (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
This study aims to describe the relationship between participatory budgeting or participatory budgeting for budgetary slack. The population in this study were Echelon III and IV officials within the scope of the Regional Government of Majene Regency. Sampling technique is Convenience Sampling. The samples in this study were the Regional Financial and Asset Agency, the Culture and Tourism Agency, the Public Library, Archives and Documentation Service, the Cooperative, Industry and Trade Office, and the Regional Development Planning Agency with a total of 70 officials. This research was conducted with a simple regression analysis method. The results showed that Participatory Budgeting had a positive effect on Budgetary Slack. The coefficient of participatory budgeting is 11.4% with a significance level of 0.004 (<0.05).Keywords: Participative Budgeting, Budgetary Slack